Stress amongst adolescents – An alarm for health service preparedness - Jain, Seema; Jain , Bhavna (Indian Journal of Community Health, 2020)
Adolescence can be described as a transitional period from childhood to adulthood. WHO defines adolescence as the period of life between 10-19 years (1). India alone is home to more than 250 million adolescents or 20% of the global adolescent population (1). It is critically important stage of life as they face rapidly changing challenges in their social, physical mental and psychological environments. Their cultural beliefs, family structure and support, peer relationships and educational opportunities influence their behaviour and adjustment. During this stage of life, they not only develop autonomy, self-control, social interaction and learning, but also the capabilities formed in this period directly influence their mental health for the rest of their lives as many of these tend to run a chronic or relapsing course in adulthood (2).